Isoform specificity of progesterone receptor antibodies - Fabris, Victoria Teresa (2017)
Progesterone receptors (PR) are prognostic and predictive biomarkers in hormone-dependent cancers. Twomain PR isoforms have been described, PRB and PRA, that differ only in that PRB has 164 extra N-terminalamino acids. It has been reported that several antibodies empirically exclusively recognize PRA in formalinfixedparaffin-embedded (FFPE) tissues. To confirm these findings, we used human breast cancer xenograftmodels, T47D-YA and -YB cells expressing PRA or PRB, respectively, MDA-MB-231 cells modified to synthesizePRB, and MDA-MB-231/iPRAB cells which can bi-inducibly express either PRA or PRB. Cells were injectedinto immunocompromised mice to generate tumours exclusively expressing PRA or PRB. PR isoform expressionwas verified using immunoblots. FFPE samples from the same tumours were studied by immunohistochemistryusing H-190, clone 636, clone 16, and Ab-6 anti-PR antibodies, the latter exclusively recognizing PRB. Exceptfor Ab-6, all antibodies displayed a similar staining pattern. Our results indicate that clones 16, 636, and theH-190 antibody recognize both PR isoforms. They point to the need for more stringency in evaluating thetrue specificity of purported PRA-specific antibodies as the PRA/PRB ratio may have prognostic and predictivevalue in breast cancer.